Applying the Context, Input, Process, Product Evaluation Model for Evaluation, Research, and Redesign of an Online Master’s Program - Sancar Tokmak, Hatice; Baturay, H. Meltem; Fadde, Peter (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
This study aimed to evaluate and redesign an online master’s degree program consisting of 12 courses from the informatics field using a context, input, process, product (CIPP) evaluation model. Research conducted during the redesign of the online program followed a mixed methodology in which data was collected through a CIPP survey, focus-group interview, and open-ended questionnaire. An initial CIPP survey sent to students, which had a response rate of approximately 60%, indicated that the Fuzzy Logic course did not fully meet the needs of students. Based on these findings, the program managers decided to improve this course, and a focus group was organized with the students of the Fuzzy Logic course in order to obtain more information to help in redesigning the course. Accordingly, the course was redesigned to include more examples and visuals, including videos; student-instructor interaction was increased through face-to-face meetings; and extra meetings were arranged before exams so that additional examples could be presented for problem-solving to satisfy students about assessment procedures. Lastly, the modifications to the Fuzzy Logic course were implemented, and the students in the course were sent an open-ended form asking them what they thought about the modifications. The results indicated that most students were pleased with the new version of the course.